Pelvic floor muscle function after grade II tears: surface electromyography test–retest and differences between nulliparous and primiparous - Mota, Patrícia (2023)
© 2023 The Authors. Neurourology and Urodynamics published by Wiley Periodicals LLC. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.